Presence of mismatches between diagnostic PCR assays and coronavirus SARS-CoV-2 genome. Issue 6 (10th June 2020) - Khan, Kashif Aziz; Cheung, Peter
Abstract : Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2; initially named as 2019-nCoV) is responsible for the recent COVID-19 pandemic and polymerase chain reaction (PCR) is the current standard method for its diagnosis from patient samples. This study conducted a reassessment of published diagnostic PCR assays, including those recommended by the World Health Organization (WHO), through the evaluation of mismatches with publicly available viral sequences. An exhaustive evaluation of the sequence variability within the primer/probe target regions of the viral genome was performed using more than 17 000 viral sequences from around the world. The analysis showed the presence of mutations/mismatches in primer/probe binding regions of 7 assays out of 27 assays studied. A comprehensive bioinformatics approach for in silico inclusivity evaluation of PCR diagnostic assays of SARS-CoV-2 was validated using freely available software programs that can be applied to any diagnostic assay of choice. These findings provide potentially important information for clinicians, laboratory professionals and policy-makers.